ANALISIS PROMOSI PENJUALAN DALAM MENINGKATKAN MINAT BELI KONSUMEN PADA PABRIK ROTI JARWAN BAKERY DI SANGATTA - Jannatul Maryam, Ruthsari; Hasmah, Hasmah; Aisyah, Siti (Tinta Nusantara 2018 Vol.1, 2025)
The research objective to be achieved is to find out and analyze sales promotion in increasing consumer buying interest at the Jarwan Bakery Sangatta Bread Factory. The analysis method used is qualitative analysis. In this study, data analysis has been carried out simultaneously with the data collection process. The analysis flow follows the interactive analysis model as expressed by Miles and Huberman in the book by Sugiyono (2018: 246). The population in this study were 9 employees and owners of the Jarwan Bakery Sangatta Bread Factory, From the results of the analysis of the discussion conducted by the author, this study uses 4 stages, namely data collection, data reduction, data presentation and drawing conclusions. Jarwan bread factory sales have decreased, this decline is due to the large number of competitors in similar business fields who have also entered the market in the Sangatta area, similar competitors come from outside the area, such as Balikpapan, Jakarta, and others. Sales promotion is still traditional, namely word of mouth, word-of-mouth or promotion that relies on word-of-mouth communication is a form of promotion. Where similar competitors have already used online marketing media. Consumers' buying interest in Jarwan bakery increased after learning information about quality bread products through friend-to-friend promotions